Implementación de biomasa y energía solar en una vivienda ecológica temporal en la empresa Autopartes y Autogrúas FCN S.a. con una capacidad de 1.5 kW-h. - Calán Pozo, Juan Carlos (2018)
The present research project is to implement “Biomas” and solar energy into a temporary green home with a capacity of 1.5 kW·h; the equipment was tested under different climatic conditions. The taking results was followed through at an interval of 5 minutes for the heat pump and in the case of the photovoltaic system was tabulated every 20 minutes from 6:20 to 18:20 h for the selection of the optimum angle in Tulcán City where were carried out four days of test with 0’, 5’, 10’, 15’, 30’ and 45 angles. Input current intensity can vary from 7.71 to 15.58 to the maximum temperature of water reached in the tank of 100 liters was 45.2’ C in the morning with an average radiation of 433.21 W·m-2 and a room temperature of 13.47’ C, over a period of 120 minutes. On the other hand, during the night when the radiation is 0 W·m-2 in the heat water pump operation the water reached a temperature of 31.2’C. The Photovoltaic system can test a real voltage demand of 2.44 kW·h which is an enough power to keep the energy required by a person. Implement a solar PV leads to very high startup investment costs, this investment will be recovered over a period of 4 years, 6 months and 17 days. The long life of the equipment can contribute to the environment, leaving issue of 0.87 tonnes of CO2 per year, can take advantage of 20 years about clean and free energy as the energy taken from the sun.